188k views
1 vote
Let the function q be given by q(x) = -2(-3x + 2) and let y be the image of x under q. Find the formula for q-1.

Let the function q be given by q(x) = -2(-3x + 2) and let y be the image of x under-example-1
User AlexOwl
by
6.4k points

1 Answer

2 votes

Given:-


q(x)=-2(-3x+2)

To find:-


q^(\prime)(x)

So now ,


y=-2(-3x+2)

So now we find the value of x. so we get,


\begin{gathered} y=-2(-3x+2) \\ y=6x-4^{} \\ y+4=6x \\ (y+4)/(6)=x \end{gathered}

So the required solution is,


q^(\prime)(x)=(y+4)/(6)

User EdStevens
by
6.2k points